KOMPARASI PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING DENGAN PROBLEM SOLVING TERHADAP HASIL BELAJAR DASAR LISTRIK DAN ELEKTRONIKA SISWA KELAS X SMKN 5 PADANG - Luthfi Rahman; Putra Jaya; Almasri Almasri (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2018)
This research was focusing in the difference of learning outcome, specially on Basic Electrical and Electronic, in first grade at SMKN 5 Padang. The purpose was to reveal the difference of Problem Solving and Problem Posing learning model when they were implemented. By using quasi experimental dengan nonprobability sampling tecnique, was obtained two experiment classes. The first experiment class was X TAV 1E3A, which was implemented Problem Posing learning model. The second experiment class was X TAV 1E3B, which was implemented Problem Solving learning model. The primary data was measured by post test based on basic competence of subject. Based on the t-test, complying the pre-requisite such as normality test, this research found that t>t0 (2,627 > 1,697). However, the result has shown that Problem Posing learning model was providing student’s learning outcome better than Problem Solving. Therefore, the Problem Posing learning model is better implemented than Problem Solving.Keywords: Problem Posing, Problem Solving, Learning Outcome.